Adding a Web-Based Virtual Reality Classroom Experience to a Hybrid, Blended Course Modality - Laura Huisinga (Virtual Worlds, 2023)
The blended classroom is a unique space for face-to-face (F2F) interaction and online learning. The blended classroom has three distinct interaction types: in-person synchronous, virtual synchronous, and virtual asynchronous; each of these modalities lends itself to different forms of extended reality. This case study looks at using a virtual reality (VR) classroom for an online synchronous weekly meetings for three upper-division or advanced (junior and senior level) higher education design classes at a university. The use of social web VR for a classroom can offer a collaborative, real-time environment that bridges the gap between virtual video conferences and gaming platforms. This paper examines how to use social web VR in a virtual classroom. Mixed methods were used to collect usability data at the end of the semester survey. The system usability scale (SUS) and several qualitative questions gathered student feedback. Overall, the students enjoyed using the VR classroom, but audio issues seemed to be the most significant pain point. While the overall response was positive, this study will address several areas for improvement from both the student and instructor perspectives. Social, web-based VR offers promising potential. Designing a human-centered virtual environment and considering all participants’ total user experience is critical to a successful learning tool.